Dietary acid load in a group of kidney transplantation candidates (Research, Society and Development, 2021)
Objective: The objective of the study was to estimate and analyze the Potential Renal Acid Load (PRAL) of the diet in patients maintenance hemodialysis who are candidates for transplantation. Methodology: A cross-sectional study was conducted. The sample was separated in terciles of the PRAL. For the association between the PRAL and the independent variables, non-adjusted multinomial logistic regression and adjusted by potential confounders were implemented. It was assumed a p< 0,05 for statistical significance. Results: It was noticed that protein (g), the protein /kg of weight (g/kg), % of animal and vegetal protein, the phosphorus (mg), the lipid (g), and the carbohydrate (g) showed differences between the terciles (p